An empirical investigation on EDI determinants and outcomes in Malaysian industry - Abdul Hamid, Abu Bakar (Penerbit UTM Press, 2009)
Government involvement is the main cause for the EDI acceptance in Southeast Asian countries (United Nation of Economic and Social Commission for Asia and Pacific - UNESCAP, 1996). This is significantly different from the EDI developments in the western countries in which private sector involvement in EDI is substantial (UNESCAP, 1996). As an initial step to spur EDI implementation in private sector, the Malaysian Government has imposed all companies that engage in international trade to implement EDI by doing electronic customs declarations through CIS (Customs Information System) DagangNet. For this, the Government also spent over RM 300 million to fully implement EDI nationwide (Star, 2003 December 3). Nevertheless, such implementation is not successful and it has been claimed that “EDI is not yet fully implemented even though it had been initiated since late 1990s, besides electronic data is also still not recognized for legal customs declaration purposes even if it was meant for paperless and electronic customs declarations” (Star, 2003 December 3). To date, there are dual customs declarations, both electronic and manual, in practices where the sole typical electronic transaction is registration of the customs form (Jimmy, 2005; Star, 2005 July 11). This is in contrast with electronic customs declarations by other countries such as Hong Kong, Korea and Singapore where there is a full electronic declaration including electronic payment for declarations charges (Jimmy, 2005; Star, 2005 July 11; Chau, 2001).